2000
DOI: 10.1016/s0029-7844(00)01074-7
|View full text |Cite
|
Sign up to set email alerts
|

Cervical length at 16–22 weeks' gestation and risk for preterm delivery

Abstract: Transvaginal measurement of cervical length during routine ultrasound at 16-22 weeks' gestation in asymptomatic gravidas might help identify women at risk for spontaneous preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 12 publications
3
67
1
6
Order By: Relevance
“…The TVU report may include funneling of the sonographic internal os, so that the following parameters may be reported: functional CL, which is the closed part of the cervix; funnel length, which is the open part of the cervix and funnel width (Figure 1) [20]. Studies have established that progressive cervical effacements precede uterine contraction by several weeks in both normal and sPTB [21,22]. Overall, functional CL is the preferred method in establishing the risk of sPTB, considering that, if funneling is present, the CL is almost always short (Figure 2).…”
Section: Technical and Clinical Aspects Of Transvaginal Cervical Sonogrmentioning
confidence: 99%
“…The TVU report may include funneling of the sonographic internal os, so that the following parameters may be reported: functional CL, which is the closed part of the cervix; funnel length, which is the open part of the cervix and funnel width (Figure 1) [20]. Studies have established that progressive cervical effacements precede uterine contraction by several weeks in both normal and sPTB [21,22]. Overall, functional CL is the preferred method in establishing the risk of sPTB, considering that, if funneling is present, the CL is almost always short (Figure 2).…”
Section: Technical and Clinical Aspects Of Transvaginal Cervical Sonogrmentioning
confidence: 99%
“…Sonographic CL measurement and its shortening in the second trimester is one of the strongest predictors for PTD in low-risk population [5,[14][15][16][17]. The "cut-off" value of 25 mm for CL is the commonest and widely used in majority of previous studies that investigated the relation of CL and incidence of PTD [5,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier investigation we found positive correlation between increased electrical activity of the uterine body and shortening of the CL [3]. Additionally, several investigators have reported the relation and usefulness of second trimester sonographic assessment of the CL for prediction of PTD in asymptomatic low-risk population [5,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 91%
“…At 22-24 weeks gestation, the 10 th percentile is approximately 25 mm, although between 16 and 22 weeks (when women typically receive their anatomic survey and cervical length screening) the 10 th percentile is 30 mm. [1][2][3] Among nulliparous women, a short cervix is the risk factor with the highest population attributable risk for preterm birth. 4 Nevertheless, even though the presence of a short cervix increases the chance of spontaneous preterm birth, many nulliparous women with this finding will still deliver at term.…”
Section: Abstract Cervical Length; Prediction; Spontaneous Preterm Birthmentioning
confidence: 99%